2012
DOI: 10.1371/journal.pone.0033577
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of microRNA-26a Promotes Mouse Hepatocyte Proliferation during Liver Regeneration

Abstract: BackgroundInadequate liver regeneration (LR) is still an unsolved problem in major liver resection and small-for-size syndrome post-living donor liver transplantation. A number of microRNAs have been shown to play important roles in cell proliferation. Herein, we investigated the role of miR-26a as a pivotal regulator of hepatocyte proliferation in LR.Methodology/Principal FindingsAdult male C57BL/6J mice, undergoing 70% partial hepatectomy (PH), were treated with Ad5-anti-miR-26a-LUC or Ad5-miR-26a-LUC or Ad5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 43 publications
3
50
0
1
Order By: Relevance
“…Therefore, in this experiment, the expression of miRNAs in bovine pituitary was examined to determine which gene regulates pituitary development. Comprehensive analysis of the results using various software programs can improve the prediction accuracy of candidate miRNA target genes (Zhou et al, 2012;Altmäe et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in this experiment, the expression of miRNAs in bovine pituitary was examined to determine which gene regulates pituitary development. Comprehensive analysis of the results using various software programs can improve the prediction accuracy of candidate miRNA target genes (Zhou et al, 2012;Altmäe et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For example, critical lipid-sensitive transcription factors controlling hepatic metabolism, such as the LXR and PPAR families, have been shown to be functional targets of multiple miRNAs (LXR ␣ : miR-613; PPAR ␣ : miR-21, miR-10b, miR-141; PPAR ␥ : miR-23a, miR-27b, miR-130) ( 85,(94)(95)(96)(97)(98)(99). Moreover, complex feedback loops between transcription factors and miRNAs appear to control hepatocyte differentiation and possibly other aspects of liver biology (100)(101)(102). Several other canonical miRNAs have been shown to infl uence lipid metabolic pathways, including miR-122, miR-370, miR-378, and miR-758, and they are comprehensively discussed in numerous recent review articles ( 43-45, 94, 103 ).…”
mentioning
confidence: 99%
“…Several studies have shown that miR-26a family members could suppress tumorigenesis in liver cancer cells and B lymphoma cells, and expression of miR-26a was also found to be significantly declined after 70% PH [39]. Adenovirusin 5 (Ad5)-anti-miR-26a-LUC was utilized to downregulate miR-26a in the mouse liver which resulted in enhanced proliferation of hepatocytes and improved liver function characterized by reduced serum aspartate aminotransferase (AST), alanine aminotransferase (ALT) and total bilirubin (T-Bil) during PH.…”
Section: Mir-26a Inhibits Hepatocyte Proliferation By Repressing Cyclmentioning
confidence: 99%